Whole-exome sequencing reveals novel variants of monogenic diabetes in Tunisia: impact on diagnosis and healthcare management - Kheriji, Nadia; Dallali, Hamza; Gouiza, Ismail; Hechmi, Meriem; Mahjoub, Faten; Mrad, Mehdi; Krir, Asma; Soltani, Manel; Trabelsi, Hajer; Hamdi, Walid; Bahlous, Afef; Ben Ahmed, Melika; et al. (Frontiers in Genetics, 2023)
Idiopathic type 1 diabetes was also identified in one patient. Conclusion: In this study, we emphasized the importance of genetic screening for MD in patients with familial history of diabetes mainly among admixed and under-represented populations living in Low-and Middle-Income countries. An accurate diagnosis with molecular investigation of MD may improve the therapeutic choice for better management of patients and their families. Additional researche and rigorous investigations are required to better understand phyisiopathological mechanisms of MD and to implement efficient therapies that takes into account genomic context and other related factors.